2022
DOI: 10.3390/ijms23158463
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α(1,6)fucosyltransferase: Effects on Cell Proliferation, Migration, and Adhesion in an SW480/SW620 Syngeneic Colorectal Cancer Model

Abstract: The present study explored the impact of inhibiting α(1,6)fucosylation (core fucosylation) on the functional phenotype of a cellular model of colorectal cancer (CRC) malignization formed by the syngeneic SW480 and SW620 CRC lines. Expression of the FUT8 gene encoding α(1,6)fucosyltransferase was inhibited in tumor line SW480 by a combination of shRNA-based antisense knockdown and Lens culinaris agglutinin (LCA) selection. LCA-resistant clones were subsequently assayed in vitro for proliferation, migration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 69 publications
5
23
0
Order By: Relevance
“…Another aspect to highlight is the correlation between polylactosamine levels and enhanced invasion and metastasis, as seen in SW620, LS174T, and LoVo CRC cells. 86 In a previous study, we reported increased proliferation, colony formation, and a more mesenchymal phenotype in FUT8knockdown SW480 cells, 28 which is consistent with the current findings of highly branched/polylactosamine N-glycans in SW480 cells defective in FUT8 expression. Contrarily, FUT8attenuated SW620 cells appear to exceed the regulatory capabilities of FucT-8, as previously suggested 28,29 since the currently observed modifications in the antenna profile did not worsen their natural metastatic behavior.…”
Section: ■ Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Another aspect to highlight is the correlation between polylactosamine levels and enhanced invasion and metastasis, as seen in SW620, LS174T, and LoVo CRC cells. 86 In a previous study, we reported increased proliferation, colony formation, and a more mesenchymal phenotype in FUT8knockdown SW480 cells, 28 which is consistent with the current findings of highly branched/polylactosamine N-glycans in SW480 cells defective in FUT8 expression. Contrarily, FUT8attenuated SW620 cells appear to exceed the regulatory capabilities of FucT-8, as previously suggested 28,29 since the currently observed modifications in the antenna profile did not worsen their natural metastatic behavior.…”
Section: ■ Discussionsupporting
confidence: 90%
“…71 In correspondence with the increased levels of α (2,6)-sialylation in the FUT8-attenuated clones of the SW480 and SW620 lines (Figure 3C), the results of functional assays indicated a reduced migration capacity in our SW480 FUT8knockdown cells. 28 As for the likely presence of bisecting GlcNAc residues in our N-glycome results, a significant reduction in oligosaccharide structures fulfilling the Hex = HexNAc relationship was shown in the FUT8-attenuated clones of the SW620 line. A close relationship has been previously described between the function of FucT-8 and N-acetylglucosaminyltransferase III (GlcNAc-T III) since both act directly on the N-glycan core.…”
Section: ■ Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Increased core fucosylation, along with an increase in salivary acidification and branch glycan structure, is the most frequently occurring cancer-related change among protein glycosylation [10]. The interaction of FUT8 with the proliferation and migration of various tumor cells and its epithelial-mesenchymal transition (EMT) have been studied [61][62][63]. In some cancers, FUT8 expression is significantly higher than in paracancerous tissues or cells and affects cell invasion, metastasis, and drug resistance [12,17,64].…”
Section: Discussionmentioning
confidence: 99%